The Effectiveness of the Karamunting Genzi Parenting Monitoring Card Model for Undernourished Children Receiving Local-Based Supplementary Feeding - Zenderi Wardani; Ori Pertami Enardi; Ratmawati (Institut Citra Internasional, 2025)
The reduction in wasting prevalence in Pangkalpinang City from 5.1% in 2021 to 4.9% in 2022 was statistically insignificant, reflecting a marginal decline of only 0.2%, still near the threshold.Pangkal Balam Health Center allocated the highest budget to serve 59 undernourished children under five. This study aimed to evaluate the implementation of a nutrition education model using the